2000
DOI: 10.1016/s0248-4900(01)01113-3
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of connective tissue stromas to sustain myelopoiesis depends both upon the growth factors and the local intercellular environment

Abstract: In adults, haemopoiesis is located in the bone marrow, where it is tightly regulated by cytokines and by a physical association of haemopoietic progenitors with the stroma. However, in pathological situations, haemopoiesis can be partly or fully dislodged to peripheral tissues. It is not clear which are the requirements for a given peripheral stroma to sustain haemopoiesis. Using the growth factor-dependent cell line FDC-P1, we have compared the myelopoietic capacities of a murine bone marrow-derived cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 33 publications
(41 reference statements)
2
31
0
Order By: Relevance
“…Fibronectin has been reported to induce proliferation of mature DC (10). Although fibronectin had no effect in our system, it is possible that other matrix proteins such as heparin sulfate proteoglycans, which are produced by S17 cells and can modulate GM-CSF activity, are involved (39,40).…”
Section: Discussionmentioning
confidence: 77%
“…Fibronectin has been reported to induce proliferation of mature DC (10). Although fibronectin had no effect in our system, it is possible that other matrix proteins such as heparin sulfate proteoglycans, which are produced by S17 cells and can modulate GM-CSF activity, are involved (39,40).…”
Section: Discussionmentioning
confidence: 77%
“…Our previous studies, as well as studies from other laboratories, have shown that the ability of a stroma to sustain myelopoiesis depends upon the stroma-associated glycoconjugates, and glycosaminoglycans in particular (23,(27)(28)(29). In order to determine whether the differences in the K M values for membrane-bound versus spontaneously released DPP-IV were a consequence of the loss of interactions of the enzyme with the cell membrane-associated molecules such as proteoglycans, we first assayed the effect of sulfated glycosaminoglycans on the stroma-derived enzyme K M .…”
Section: Dependence Of Dpp-iv Activity On the Environmentmentioning
confidence: 99%
“…The former two cell types sustain myelopoiesis whilst the last one does not. These cells were isolated, maintained, and characterized as previously described (21)(22)(23). Cells were maintained routinely in Dulbeccos minimum essential medium (DMEM; Sigma, St. Louis, MO, USA) supplemented with 10% fetal bovine serum (FBS; Cultilab, Campinas, SP, Brazil).…”
Section: Cell Culturesmentioning
confidence: 99%
“…Considerable evidence implicates the sulfated GAGs heparan sulfate and heparin in the modulation of the biological activity of GM-CSF (9,10,33,34). However, to date no GAGbinding sites in GM-CSF have been structurally identified.…”
Section: Discussionmentioning
confidence: 99%